Human immune responses against Shigella and enterotoxigenic E. coli: Current advances and the path forward. Issue 49 (14th December 2017) - McArthur, Monica A.; Maciel, Milton; Pasetti, Marcela F.
Abstract: Robust and well-established immunological assays and firm immune correlates of protection that can predict disease outcome and/or vaccine efficacy are essential to adequately assess human immune responses to infection and vaccination. The availability of reagents and calibrated controls is also critically important to standardize assays and generate comparable results among different laboratories. The workshop "Human Immune Responses against Shigella and ETEC: Current Advances and the Path Forward" held during the VASE meeting provided an opportunity to disseminate and discuss recent advances in the field of Shigella and ETEC immunology, identify research needs, and propose collaborative activities to advance the field. Four presentations featured current knowledge on humoral and cellular immune responses to Shigella and ETEC during infection and vaccination. A discussion followed on immunological methods relevant for clinical studies, immune parameters associated with protection, harmonization of assays among laboratories, and availability of reagents and standards. Specific recommendations proposed to facilitate "the path forward" included supporting communication among scientists, harmonization of assays and sharing of protocols, the creation of a repository of reagents and calibrated controls and distribution of such material to the research community, and expansion of exploratory studies to better understand the interactions between these pathogens and the human immune system and the ensuing responses.